The work of support specialists with adopted children with disabilities and their families. The problems of foster families support who have adopted children with ASD - Okoneshnikova N.M (Moscow State University of Psychology and Education, 2017)
The desire of having a family is crucial for foster families and adopted children with disabilities. But the cases of refusing an adopted child with disabilities are not uncommon. A group of problems faced by foster families, who have adopted disabled child, are shown. The issues of comprehensive support for a foster family and their disabled children are considered. The importance of cooperation between specialists and a foster family for the socialization and development of a child with autism spectrum disorders is marked.